PENGGUNAAN STRATEGI KNOW, WANT TO KNOW AND LEARNED (KWL) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN KELAS III SEKOLAH DASAR - Diah Pujasari; Ryan Dwi Puspita (JESA-Jurnal Edukasi Sebelas April, 2023)
This research objective is to improve the ability of reading comprehension on the students of third grade at 045 Pasirkaliki Elementary School by using the know, want to know and learned (KWL) learning strategy. The subjects were 28 students in class III A 045 Pasirkaliki Elementary School. This study utilizes is Classroom Action Research (PTK) which consist of two cycles, each cycle consisting of four stages. Four stage is planning, implementing the action, observing and reflecting. Data collection techniques used test in first cycle and second cycle, observation sheets, student response questionnaire and interview sheets. Pre-action score was 64.11 the first cycle score was 72.5 and the second cycle was 81,8. Based on the results of the study, it can be concluded that the applying of know, want to know and learned (KWL) learning strategy to improve reading comprehension skills on third grade students at 045 Pasirkaliki Elementary School is quite effective.